Water masses in the Canary Current Large Marine Ecosystem - Pastor, María V.; Vélez-Belchí, Pedro; Hernández-Guerra, Alonso (IOC-UNESCO, 2015)
In the Canary Current Large Marine Ecosystem (CCLME) water masses of very different origin converge. In the upper layer, the North Atlantic Central Waters (NACW) and the South Atlantic Central Waters (SACW); at intermediate levels the Antarctic Intermediate Water (AAIW) and the warmer and saltier Mediterranean Water (MW); and at the deeper levels the North Atlantic Deep Water (NADW). Here we describe the origin and distribution of these waters masses. Published